Self Adjustment of High School Students with Peers and Its Implications in Guidance and Counseling Service - Fitria Fitria; Zikra Zikra (Jurnal Neo Konseling, 2021)
Self Adjustment is an individual's effort to establish good relationships by changing circumstances that can change individuals to enter into a social environment in their interactions. This research is motivated by the phenomenon of students who have a low adjustment to their peers. This study aims to describe how the general picture of the adjustment of students with their peers is seen from the aspects of personal harmony, harmony with the environment and the ability to deal with tensions of conflict and frustration.This research uses descriptive quantitative research. The population in the study were all students of SMA Adabiah Padang, amounting to 587 students and the sample in this study amounted to 238 SMA Adabiah Padang students who were selected using proportional random sampling technique. The instrument used in this study was a questionnaire about students' adjustment to the Likert scale model. The data analysis technique used descriptive statistical techniques.This study describes the adjustment of SMA Adabiah Padang students with their peers based on the following aspects: (1) personal harmony is in the medium category with a percentage (46%), (2) harmony with the environment is in the medium category with a percentage (41%) and ( 3) the ability to overcome conflict and frustration is in the medium category with a percentage (57%).